A thematic content analysis of how marketers promote energy drinks on digital platforms to young Australians. (29th October 2018) - Buchanan, Limin; Yeatman, Heather; Kelly, Bridget; Kariippanon, Kishan
Abstract: Objective : This study aimed to explore the nature and extent of, and level of user‐engagement with, appealing strategies used by the food industry to promote energy drinks on digital platforms. Methods : Thematic content analysis was employed to code the textual and visual elements of the data that were extracted from the online media pages of nine energy drinks, including posts on Facebook, YouTube, Twitter, and content of websites and advergames. Results : Four main themes were derived from the 624 textual and visual elements of digital marketing content of energy drink brands, including online social connectivity, desired social identity, enhancement of performance and enhancement of mood. Conclusions : Energy drinks were popular on digital platforms, as evidenced by the large volume of user‐engagement (e.g. 'likes' and 'comments') especially on social networking sites. Energy drink brands appear to target young people, given that the marketing appeals are likely attuned with young people's desires or aspirations. Implications for public health : To counter the effects of digital marketing on young people's health, regulations are needed to safeguard adolescents and young adults, as well as younger children, and consideration should be given to including all forms of marketing communication platforms, including the internet.